The Relationship Between Menarche Age And Menopause Age In The Majelis Ta’lim Congregation In Batang Kabung Ganting Neighborhood, Koto Tangah District Padang City - Shinta Pertiwi; Ariadi , Ariadi; Lili Irawati; Husna Yetti; Rahmani Welan (Publikasi Inspirasi Indonesia, 2024)
Menopause is a natural and unique period for women. Menopause occurs naturally in most women between the ages of 45 and 52 and is characterized by changes in hormonal status and the cessation of menstrual cycles. Menopause This causes a decrease in a person’s quality of life because they will experience unpleasant symptoms such as anxiety, depression, decreased desire, and concentration and vasomotor disorders. The purpose of the research is to find out the relationship between the age of menarche and the age of menopause that occurs in the congregation of the ta’lim assembly in the Batang Kabung Ganting sub-district, Koto Tangah sub-district, Padang City. This type of research is correlative analytic research. The sampling technique used a consecutive sampling technique. The minimum sample in this study amounted to 106 samples. The results showed that most respondents experienced menarche at the age of 12 years, as many as 24 respondents (22.6%). Most respondents experienced menopause at the age of 50 years, namely as many as 24 respondents (22.6%). The results of statistical tests using Pearson correlation obtained Sig. 0.000, and the calculated r result is -0,809, which means that there is a relationship between the age of menarche and the age of menopause. The result of the calculated r-value is negative -0,809, so both variables have a relationship that is very strong but contradictory, which means that the slower a person experiences menarche, the faster they will experience menopause and vice versa. In conclusion, most respondents experienced menarche at the age of 12 years, and most respondents experienced menopause at the age of 50 years.